Sakit Mata Refleksi Atas Pengalaman Pribadi Di Indonesia - Yngvesson, Finn (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
Books are capable of storing large quantities of information, both written and visual, forthousands of years. A printed book is not like digital information on a hard drive, a website, acompact disc, a photograph or an art exhibit. A printed book will last for a very long time if thematerials are acid free and it is stored properly.Sakit Mata is a project to compile my writings and paintings from the year 2009 until2013. This was a time when I traveled from America to come to graduate school in Indonesia. Ifelt that it was important to combine writing and paintings to help the reader to understand thekinds of experiences and observations about my surroundings that influenced the work. I chosea book format not only because it enabled me to combine writing with images, but also becauseof its permanence and ability to maintain cohesiveness unchanged over time. I saw many of myfriends and classmates display their paintings together in the format of a gallery show thatlasted for a week or two and then was gone. I don't want my experiences to be forgotten and mypaintings scattered in different places after a gallery show is over. I want everything to staytogether unchanged, documenting this time in my life and in the history of Indonesia.This kind of art book containing a wide variety of subjects does not serve a clearpurpose, other than the preservation and documentation of memory and artworks for the future.I hope this book can have an appeal for many kinds of people and I purposely spent a lot of timewriting the book in both Indonesian and English so that more people can understand the writtencontent.